Further aspects of the therapeutic options: [Rezension von: Rolf Kalff, Christian Ewald, Albrecht Waschke, Lars Gobisch, Christian Hopf: Degenerative lumbar spinal stenosis in older people] - Schiltenwolf, Marcus (Deutsches Ärzteblatt, 2014)
The article (1) provides a good overview of the treatment options in lumbar spinal stenosis. However, crucial aspects were not mentioned: many patients are treated with complex surgery if imaging shows spinal stenosis when what they actually have is...